Determination of internal series resistance of PV devices: repeatability and uncertainty. (30th March 2016) - Trentadue, Germana; Pavanello, Diego; Salis, Elena; Field, Mike; Müllejans, Harald
Abstract: The calibration of photovoltaic devices requires the measurement of their current–voltage characteristics at standard test conditions (STC). As the latter can only be reached approximately, a curve translation is necessary, requiring among others the internal series resistance of the photovoltaic device as an input parameter. Therefore accurate and reliable determination of the series resistance is important in measurement and test laboratories. This work follows standard IEC 60891 ed 2 (2009) for the determination of the internal series resistance and investigates repeatability and uncertainty of the result in three aspects for a number of typical photovoltaic technologies. Firstly the effect of varying device temperature on the determined series resistance is determined experimentally and compared to a theoretical derivation showing agreement. It is found that the series resistance can be determined with an uncertainty of better than 5% if the device temperature is stable within  ±0.1 °C, whereas the temperature range of  ±2 °C allowed by the standard leads to much larger variations. Secondly the repeatability of the series resistance determination with respect to noise in current–voltage measurement is examined yielding typical values of  ±5%. Thirdly the determination of the series resistance using three different experimental set-ups (solar simulators) shows agreement on the level of  ±5% for crystalline Silicon photovoltaic devices and deviations up to 15% for thin-film devices. It is concluded that the internal series resistance of photovoltaic devices could be determined with an uncertainty of better than 10%. The influence of this uncertainty in series resistance on the electrical performance parameters of photovoltaic devices was estimated and showed a contribution of 0.05% for open-circuit voltage and 0.1% for maximum power. Furthermore it is concluded that the range of device temperatures allowed during determination of series resistance in IEC 60891 should be further restricted.